Interações de níveis de ácidos orgânicos e de proteína digestível das dietas no desempenho e eficiência de utilização de nutrientes para tilápia do Nilo - Amorim, Daniela Bezerra de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The subject of this trial was to determine the impact of the inclusion of a commercial organic acids blend (BAO) (0.0%, 1.0%, 2.0% and 3.0%) on three diets containing different levels of digestible protein (DP) (24.30%, 26.81% and 29.32%) on the productive performance, body composition, nutrient digestibility, protein efficiency, physiological indices and intestinal histomorphometry of Nile tilapia. A total of 468 Nile tilapia juveniles were used, with initial mean weight of 16.20 ± 8.03 g, distributed in 36 tanks. The experimental design was completely randomized with twelve treatments and three replicates, in a 4x3 factorial scheme. Fish were fed four times daily until apparent satiety for 95 days. There was no effect of the interaction between the OAB inclusion levels and the protein contents of the diets on the means of: feed conversion (FC), protein efficiency rate (PER), crude protein retention efficiency (CPRE), gross energy retention efficiency (GERE), ethereal extract in weight gain (EEWG), crude protein in weight gain (CPWG), villus width (VW), muscle tunica (MT) and physiological indices. There was an effect of the interaction between the factors studied on mean weight gain (WG), feed intake (FI), specific growth rate (SGR), carcass phosphorus (P) and apparent digestibility coefficients (ADCCP, ADCGE and ADCMM). The highest means were obtained with the use of 1% OAB together with the 29.32% DP content. For intestinal histomorphometry, there was interaction between the factors. The best means for the number of goblet cells (GC) and villous height (VH) were obtained in diets with 29.32% of CP and the inclusion of 3% of OAB.

O objetivo do presente estudo foi determinado o impacto da inclusão crescente de um blend comercial de ácidos orgânicos (BAO) (0,0%, 1,0%, 2,0% e 3,0%) em três dietas contendo diferentes teores de proteína digestível (PD) (24,30%; 26,81% e 29,32%) sobre o desempenho produtivo, composição corporal, digestibilidade de nutrientes, taxa de eficiência proteica, índices fisiológicos e sobre histomorfometria intestinal de revertidos de tilápia do Nilo. Foram utilizados 468 juvenis de tilápia do Nilo, com peso médio inicial de 16,20 ± 8,03 g, distribuídos em 36 tanques. O delineamento experimental foi inteiramente casualizado com doze tratamentos e três repetições, em esquema fatorial 4x3. Os peixes foram alimentados quatro vezes ao dia até saciedade aparente por 95 dias. Não houve efeito da interação entre os teores de inclusão do BAO e os teores proteicos das dietas sobre as médias de: conversão alimentar (CA), taxa de eficiência proteica (TEP), eficiência de retenção de proteína bruta (ERPB), eficiência de retenção de energia bruta (EREB), extrato etéreo no ganho de peso (EEGP), proteína bruta no ganho de peso (PBGP), largura de vilosidades (LV), túnica muscular (TM) e sobre os índices fisiológicos. Houve efeito da interação entre os fatores estudados sobre as médias de ganho de peso (GP), consumo de ração (CR), taxa de crescimento específico (TCE), fósforo na carcaça (P) e coeficientes de digestibilidade aparente (CDAPB, CDAEB e CDAMM), sendo as maiores médias obtidas com o uso de 1% de BAO juntamente com o teor de 29,32% de PD. Para a histomorfometria intestinal, houve interação entre os fatores. As melhores médias para o número de células caliciformes (CC) e a altura das vilosidades (AV) foram obtidos nas dietas com 29,32% de PD e a inclusão de 3% do BAO.
Interactions of organic acid levels and dietary digestible protein in performance and nutrient utilization efficiency for Nile tilapia
Keywords: Aditivo alimentar; Desempenho produtivo; Nutrição de peixes; Oreochromis niloticus